Preparation method of diethylene glycol
By preparing and applying SO42-/ZnFeO4-ZrO2 catalysts, problems such as flammable and explosive ethylene oxide and corrosiveness of traditional proton acid catalysts in the prior art are solved, and efficient, environmentally friendly and stable production of ethylene glycol dehydration reaction is achieved.
Patent Information
- Application Number
- CN202311198601.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-15
AI Technical Summary
In the prior art, the method of using ethylene oxide as the initial raw material for preparing oligoethylene glycol is flammable and explosive, carcinogenic, long process flow, high energy consumption and serious side reactions. At the same time, traditional protonic acid catalysts have problems such as corrosiveness, toxicity and difficulty in treating waste acid wastewater in the ethylene glycol dehydration reaction.
The SO42-/ZnFeO4-ZrO2 catalyst was prepared and applied to the ethylene glycol dehydration reaction to improve the conversion of ethylene glycol and the selectivity of diethylene glycol. The catalyst prepared ZnFeO4 by high-temperature calcination method, loaded with ZrO2 by impregnation method, and immersed by H2SO4 solution to obtain SO42-/ZnFeO4-ZrO2.
The catalyst has high activity, good selectivity and stability, can improve the efficiency of ethylene glycol dehydration reaction, is suitable for large-scale production, and reduces waste generation.
Smart Images

Figure CN119638557A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing diethylene glycol, and belongs to the field of chemical industry. Background Art
[0002] Low-molecular-weight glycols such as diethylene glycol (DEG, structural formula HOCH3CH3OCH3CH3OH) and triethylene glycol (TEG, structural formula HOCH3CH3OCH3CH3OCH3CH3OH) are mainly used as solvents for various purposes, gas dehydrating agents, aromatic hydrocarbon separation and extraction agents, textile softeners, finishing agents, and are also used as antifreeze components in brake fluids and compressor lubricants. They can also be used to prepare cleaning agents and as dispersant solvents in other daily chemicals such as inks. In addition, low-molecular-weight glycol molecules contain two functional groups, ether bonds and hydroxyl groups, which give them unique physical and chemical properties. They are widely used in the preparation of a variety of chemicals such as rubber and resin plasticizers, polyester resins, fiberglass, and urethane foams. They are important raw materials in the petrochemical, rubber, plastic, textile, coating, and adhesive industries.
[0003] At present, domestic diethylene glycol and triethylene glycol only come from the by-products of ethylene glycol produced by hydration of ethylene oxide (EO), and the content of diethylene glycol in the by-products is about 9%, and that of triethylene glycol is about 1%. In addition, ethylene oxide is flammable and explosive and is a type of carcinogen, which is not conducive to storage and transportation; the process is long, energy consumption is high, and it is difficult to control the depth of reaction. Therefore, the method of preparing oligoethylene glycol using ethylene oxide as the initial raw material has been limited in application. The technology of preparing diethylene glycol by dehydration of ethylene glycol has good industrial application prospects.
[0004] As we all know, the protonic acid mainly used in traditional industry has disadvantages such as corrosiveness and toxicity. Using it in the ethylene glycol dehydration reaction not only causes great corrosion to the equipment, but also causes serious side reactions. At the same time, the large amount of waste acid and wastewater generated by this method is difficult to handle, which not only increases industrial costs but also causes a waste of some resources.
[0005] There are still few solid acid catalysts reported in the literature for catalyzing the dehydration reaction of ethylene glycol. Solid acid catalysts have become the focus of researchers due to their many advantages such as high activity, high selectivity and easy separation. With the advancement of science and technology and the improvement of people's environmental awareness, in chemical production, a solid acid catalyst with advantages such as recyclability and reuse is gradually replacing traditional proton acid catalysts. Summary of the invention
[0006] This application prepares SO4 2- / ZnFeO4-ZrO2 catalyst and its application in the preparation process of diethylene glycol have great significance. The catalyst has good activity, high ethylene glycol conversion rate and diethylene glycol selectivity, and good stability.
[0007] According to one aspect of the present application, a method for preparing diethylene glycol is provided, the preparation method comprising:
[0008] Contacting ethylene glycol with a catalyst to react and obtain the diethylene glycol;
[0009] The catalyst is SO4 2- / ZnFeO4-ZrO2.
[0010] Optionally, the SO4 2- / ZnFeO4-ZrO2 is obtained by treating ZnFeO4 with surface loaded ZrO2 by immersion in sulfuric acid.
[0011] Optionally, the preparation method of the catalyst includes: preparing ZnFeO4 by a high temperature calcination method, loading ZrO2 on the surface of ZnFeO4 by an impregnation method, preferably obtaining the catalyst by impregnation with a H2SO4 solution.
[0012] Optionally, the SO4 2- The preparation method of ZnFeO4-ZrO2 comprises the following steps:
[0013] (1) drying and calcining a mixture containing a zinc source, an iron source and a solvent I to obtain ZnFeO4;
[0014] (2) drying II and calcining II the mixture containing the zirconium source, ZnFeO4 and solvent II to obtain ZnFeO4-ZrO2;
[0015] (3) impregnating ZnFeO4-ZrO2 with H2SO4 solution, drying III, calcining III, and obtaining the SO4 2- / ZnFeO4-ZrO2.
[0016] Optionally, the zinc source is selected from at least one of zinc nitrate, zinc sulfate and zinc oxide.
[0017] Optionally, the iron source is selected from at least one of ferric nitrate, ferric sulfate and ferric oxide.
[0018] Optionally, the zirconium source is selected from zirconium sulfate and / or zirconium nitrate.
[0019] Optionally, in step (1), the molar ratio of the zinc source to the iron source is (0.9-2):1.
[0020] Optionally, the molar ratio of the zinc source to the iron source is selected from any value of 0.9:1, 1:1, 1.9:1, 2:1 or a range between any two of the above values.
[0021] Optionally, the solvent I is selected from at least one of methanol, ethanol and acetone.
[0022] Optionally, the temperature of the drying I is 80-110° C., and the time of the drying I is 2-5 hours.
[0023] Optionally, the drying temperature I is selected from any value among 80°C, 90°C, 100°C, 110°C or a range between any two of the above values.
[0024] Optionally, the drying time I is selected from any value among 2h, 3h, 4h, 5h or a range value between any two of the above.
[0025] Optionally, the temperature of the calcination I is 600-1200° C., and the time of the calcination I is 4-8 hours.
[0026] Optionally, the calcination temperature I is selected from any value of 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or a range between any two of the above values.
[0027] Optionally, the calcination time I is selected from any value among 4h, 5h, 6h, 7h, 8h or a range value between any two of the above.
[0028] Optionally, in the step (2), in the ZnFeO4-ZrO2, the mass ratio of ZnFeO4 to ZrO2 is 100:(3-20).
[0029] Optionally, the mass ratio of ZnFeO4 to loaded ZrO2 is 100:(3-20).
[0030] Optionally, the mass ratio of ZnFeO4 to loaded ZrO2 is selected from any value among 100:3, 100:5, 100:7, 100:9, 100:11, 100:13, 100:15, 100:18, 100:20 or a range between any two of the above.
[0031] Optionally, the solvent II is selected from ethanol and / or water.
[0032] Optionally, the temperature of the drying II is 80-110° C., and the time of the drying II is 2-5 hours.
[0033] Optionally, the drying temperature II is selected from any value of 80°C, 90°C, 100°C, 110°C or a range between any two of the above values.
[0034] Optionally, the drying time II is selected from any value among 2h, 3h, 4h, 5h or a range between any two of the above.
[0035] Optionally, the temperature of the calcination II is 500-600° C., and the time of the calcination II is 4-8 hours.
[0036] Optionally, the temperature of the calcination II is selected from any value of 500° C., 550° C., 600° C., or a range between any two of the above values.
[0037] Optionally, the calcination II time is selected from any value of 4h, 5h, 6h, 7h, 8h or a range between any two of the above.
[0038] Optionally, in step (3), the solid-liquid ratio of the ZnFeO4-ZrO2 to H2SO4 solution is 1:20-30 g / ml.
[0039] Optionally, the solid-to-liquid ratio of the ZnFeO4-ZrO2 to H2SO4 solution is selected from any value of 1:20 g / ml, 1:25 g / ml, 1:30 g / ml, or a range between any two of the above.
[0040] Optionally, the concentration of the H2SO4 solution is 0.1-2M.
[0041] Optionally, the concentration of the H2SO4 solution is selected from any value among 0.1M, 0.3M, 0.5M, 0.7M, 0.9M, 1.1M, 1.3M, 1.5M, 1.7M, 2.0M or a range between any two of the above.
[0042] Optionally, the immersion time is 4 to 24 hours.
[0043] Optionally, the immersion time is any value among 4h, 8h, 12h, 16h, 20h, 24h, or a range between any two of the above.
[0044] Optionally, in step (3), the temperature of drying III is 80 to 110° C., and the time of drying III is 2 to 5 hours.
[0045] Optionally, the drying temperature of III is selected from any value of 80°C, 90°C, 100°C, 110°C or a range between any two of the above values.
[0046] Optionally, the drying time of III is selected from any value among 2h, 3h, 4h, 5h or a range between any two of the above;
[0047] Optionally, the temperature of calcining III is 400-600° C., and the time of calcining III is 3-6 hours.
[0048] Optionally, the temperature of calcining III is selected from any value of 400°C, 450°C, 500°C, 550°C, 600°C or a range between any two of the above values.
[0049] Optionally, the calcination time of III is selected from any value of 3h, 4h, 5h, 6h or a range between any two of the above.
[0050] Optionally, the reaction temperature is 80-200°C.
[0051] Optionally, in the reaction, the N2 flow rate is 0-30 ml / min.
[0052] Optionally, in the reaction, the N2 flow rate is selected from any value of 0 ml / min, 5 ml / min, 10 ml / min, 15 ml / min, 20 ml / min, 25 ml / min, 30 ml / min or a range between any two of the above.
[0053] Optionally, the mass space velocity of the reaction is 0.2 to 2 h -1 .
[0054] Optionally, the mass space velocity of the reaction is 0.2h -1 、0.4h -1 , 0.6h -1 、0.8h -1 , 1.0h -1 , 1.2h -1 , 1.4h -1 , 1.6h -1 , 1.8h -1 , 2.0h -1 Any value in or a range between any two of the above.
[0055] The beneficial effects of this application include:
[0056] 1) The catalyst provided in the present application can be applied to the dehydration reaction of ethylene glycol to prepare diethylene glycol, and can improve the conversion rate of ethylene glycol and the selectivity of the generated diethylene glycol.
[0057] 2) The preparation method of the catalyst provided in this application is stable, controllable and has good reproducibility.
[0058] 3) The method for preparing diethylene glycol by dehydration of ethylene glycol provided in the present application uses the catalyst provided in the present application, has a fast reaction speed and a high yield, and can be applied to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 Catalyst 1 in Example 1 of the present application # Reaction result 4# Gas chromatography-mass spectrometry diagram. DETAILED DESCRIPTION
[0060] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0061] Unless otherwise specified, the raw materials and catalysts in the examples of this application were purchased through commercial channels.
[0062] The gas chromatograph is a 7890B gas chromatograph from Agilent.
[0063] In the examples of this application, the conversion rate and selectivity are calculated as follows:
[0064] The conversion rate and selectivity calculation formula in the examples of the present application are as follows (with ethylene glycol conversion rate as the evaluation index):
[0065] Ethylene glycol conversion rate = (initial carbon number of ethylene glycol - carbon number of ethylene glycol in the product) * 100 / initial carbon number of ethylene glycol.
[0066] Diethylene glycol selectivity = carbon number of diethylene glycol*100 / ∑(carbon number of diethylene glycol+carbon number of other products).
[0067] Example 1
[0068] Taking No. 1 in Tables 1 to 3 as an example, zinc nitrate and iron nitrate in a molar ratio of 1:1 are mixed in an ethanol solution, ground and mixed after ultrasonic treatment, and placed in a 100°C oven to dry for 4 hours; then placed in a high-temperature furnace and calcined at 1000°C for 4 hours to obtain ZnFeO4. Zirconium sulfate, ZnFeO4 and deionized water are mixed and stirred (the mass ratio of ZnFeO4 to loaded ZrO2 is 100:15), placed in a 100°C oven to dry for 4 hours; then calcined at 500°C for 4 hours to obtain ZnFeO4-ZrO2. ZnFeO4-ZrO2 (solid-liquid ratio 1:20g / ml) is impregnated with 0.5M H2SO4 solution for 8 hours, filtered, placed in a 100°C oven to dry for 4 hours, and then calcined at 500°C for 3 hours to obtain SO4 2- / ZnFeO4-ZrO2, denoted as catalyst 1 # .
[0069] Table 1
[0070]
[0071] Table 2
[0072]
[0073]
[0074] The columns in Tables 1 and 2 above are explained as follows:
[0075] Zinc source: zinc nitrate (Zn1), zinc sulfate (Zn2), zinc oxide (Zn3). Iron source: ferric nitrate (Fe1), ferric sulfate (Fe2), ferric oxide (Fe3). Solvent I: methanol (solvent 1), ethanol (solvent 2), acetone (solvent 3).
[0076] Zirconium source: zirconium sulfate (Zr1), zirconium nitrate (Zr2).
[0077] Solvent II: ethanol (dissolve 2), deionized water (dissolve 4).
[0078] Drying I: Drying during the preparation of ZnFeO4.
[0079] Drying II: Drying during the preparation of ZrO2-ZnFeO4.
[0080] Calcination I: Calcination during the preparation of ZnFeO4.
[0081] Calcination II: Calcination during the preparation of ZrO2-ZnFeO4.
[0082] Table 3
[0083]
[0084]
[0085] The columns in Table 3 above are explained as follows:
[0086] Drying III: Preparation of SO4 2- / Drying during ZrO2-ZnFeO4 process.
[0087] Calcination III: Preparation of SO4 2- / calcination during the ZrO2-ZnFeO4 process.
[0088] Comparative Example 1
[0089] Zinc nitrate and iron nitrate in a molar ratio of 1:1 were mixed in an ethanol solution, ground and mixed after ultrasonic treatment, and placed in a 100°C oven to dry for 4 hours; then calcined in a high-temperature furnace at 1000°C for 4 hours to obtain ZnFeO4. Zirconium sulfate, ZnFeO4 and deionized water were mixed and stirred (the mass ratio of ZnFeO4 to loaded ZrO2 was 100:15), placed in a 100°C oven to dry for 4 hours; then calcined at 500°C for 4 hours to obtain ZnFeO4-ZrO2.
[0090] Example 2
[0091] The catalyst 1 prepared in Example 1 was used #The catalyst prepared in Comparative Example 1 was used to dehydrate ethylene glycol to prepare diethylene glycol, and the reaction parameters were changed. After the reaction was stable (reaction for 6 hours), the reaction raw materials and products were analyzed by gas chromatography online. The composition of the ethylene glycol dehydration reaction product was analyzed using an Agilent 7890B gas chromatograph (FID detector, FFAP capillary column). The reaction results are shown in Table 4.
[0092] Table 4
[0093]
[0094]
[0095] Figure 1 Catalyst 1 for this application # Reaction result 4 # GC-MS graph, from Figure 1 It can be seen that the main product diethylene glycol has a high selectivity and the by-products are all known substances.
[0096] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing diethylene glycol, characterized in that: The preparation method comprises: Contacting ethylene glycol with a catalyst to react and obtain the diethylene glycol; The catalyst is SO4 2- / ZnFeO4-ZrO2.
2. The preparation method according to claim 1, characterized in that: The SO4 2- / ZnFeO4-ZrO2 is obtained by treating ZnFeO4 with surface loaded with ZrO2 by immersion in sulfuric acid.
3. The preparation method according to claim 2, characterized in that: The SO4 2- The preparation method of ZnFeO4-ZrO2 comprises the following steps: (1) drying and calcining a mixture containing a zinc source, an iron source and a solvent I to obtain ZnFeO4; (2) drying II and calcining II the mixture containing the zirconium source, ZnFeO4 and solvent II to obtain ZnFeO4-ZrO2; (3) impregnating ZnFeO4-ZrO2 with H2SO4 solution, drying III, calcining III, and obtaining the SO4 2- / ZnFeO4-ZrO2.
4. The preparation method according to claim 3, characterized in that: The zinc source is selected from at least one of zinc nitrate, zinc sulfate and zinc oxide; Preferably, the iron source is selected from at least one of ferric nitrate, ferric sulfate and ferric oxide; Preferably, the zirconium source is selected from zirconium sulfate and / or zirconium nitrate.
5. The preparation method according to claim 3, characterized in that: In the step (1), the molar ratio of the zinc source to the iron source is (0.9-2):1; Preferably, the solvent I is selected from at least one of methanol, ethanol and acetone; Preferably, the temperature of the drying I is 80-110° C., and the drying time I is 2-5 hours; Preferably, the temperature of the calcination I is 600-1200° C., and the time of the calcination I is 4-8 hours.
6. The preparation method according to claim 3, characterized in that: In the step (2), in the ZnFeO4-ZrO2, the mass ratio of ZnFeO4 to ZrO2 is 100:(3-20); Preferably, the solvent II is selected from ethanol and / or water; Preferably, the temperature of drying II is 80-110° C., and the time of drying II is 2-5 h; Preferably, the temperature of the calcination II is 500-600° C., and the time of the calcination II is 4-8 hours.
7. The preparation method according to claim 3, characterized in that: In the step (3), the solid-liquid ratio of the ZnFeO4-ZrO2 to the H2SO4 solution is 1:20-30 g / ml; Preferably, the concentration of the H2SO4 solution is 0.1 to 2M; Preferably, the immersion time is 4 to 24 hours.
8. The preparation method according to claim 3, characterized in that: In the step (3), the temperature of drying III is 80 to 110° C., and the time of drying III is 2 to 5 hours; Preferably, the temperature of calcining III is 400-600° C., and the time of calcining III is 3-6 hours.
9. The preparation method according to claim 1, characterized in that: The reaction temperature is 80-200°C.
10. The preparation method according to claim 1, characterized in that: In the reaction, the N2 flow rate is 0-30 ml / min; Preferably, the mass space velocity of the reaction is 0.2 to 2 h -1 .
Citation Information
Patent Citations
Preparation method of supported sulfuric acid catalyst
CN106000426A
Application of SO4<2-> / WO<3->ZrO2 catalyst to preparation of diacetin from glycerol through catalytic conversion
CN108440283A
Method for continuously preparing diglycol and triglycol on fixed bed reactor
CN109053395A
Composite solid acid catalyst as well as preparation method and application thereof
CN113786847A
Method for synthesizing diethylene glycol at low temperature
CN114621061A